EJEMPLOS DE MEMORIA, MNEMOTECNIA, PALIMPSESTO E HIPERTEXTO EN PANAMÁ Y EL MUNDO: UNA METODOLOGÍA PARA LA CONSERVACIÓN - Arroyo Duarte, Silvia (2017)
This article will analyze the concepts of memory, mnemonic, palimpsest and hypertext. Sebastien Marot (2003), professor of the École d’Architecture de la Ville & des Territoires - Marne-la-Vallée (France), explains that these four reflexes are a new way of facing a design program in architecture, which prioritizes the site. These same concepts –memory, mnemonics, palimpsest and hypertext– are related to preservation, either in an urban or architectural context. The goal of this paper is to give examples (mostly in Panama City) of their use in this discipline, and relate these reflexes or characteristics to a method for the development of a conservation project. These examples will explain how memory and mnemonics preserve the spirit of place, how a palimpsest represents the history of the transformations of a territory, city or building, and how a hypertext can help organize a preservation project.